Translucent players: Explaining cooperative behavior in social dilemmas. (November 2019) - Capraro, Valerio; Halpern, Joseph Y
In the past few decades, numerous experiments have shown that humans do not always behave so as to maximize their material payoff. Cooperative behavior when noncooperation is a dominant strategy (with respect to the material payoffs) is particularly puzzling. Here we propose a novel approach to explain cooperation, assuming what Halpern and Pass call translucent players . Typically, players are assumed to be opaque, in the sense that a deviation by one player in a normal-form game does not affect the strategies used by other players. However, a player may believe that if he switches from one strategy to another, the fact that he chooses to switch may be visible to the other players. For example, if he chooses to defect in Prisoner's Dilemma, the other player may sense his guilt. We show that by assuming translucent players, we can recover many of the regularities observed in human behavior in well-studied games such as Prisoner's Dilemma, Traveler's Dilemma, Bertrand Competition, and the Public Goods game. The approach can also be extended to take into account a player's concerns that his social group (or God) may observe his actions. This extension helps explain prosocial behavior in situations in which previous models of social behavior fail to make correct predictions (e.g. conflict situations and situations where there is a trade-off between equity and efficiency).